A new method for simultaneous detection and discrimination of Bovine herpesvirus types 1 (BoHV-1) and 5 (BoHV-5) using real time PCR with high resolution melting (HRM) analysis - Marin, Maia Solange; Quintana, Silvina; Leunda, Maria Rosa; Recavarren, Mariana Ines; Pagnuco, Inti Anabela; Spath, Ernesto Juan; Perez, Sandra; Odeon, Anselmo Carlos (Elsevier, 2019)
Bovine herpesvirus types 1 (BoHV-1) and 5 (BoHV-5) are antigenically and genetically similar. The aim of this study was to develop a simple and reliable one-step real time PCR assay with high resolution melting (HRM) analysis for the simultaneous detection and differentiation of BoHV-1 and BoHV-5. Optimization of assay conditions was performed with DNA from reference strains. Then, DNA from field isolates, clinical samples and tissue samples of experimentally infected animals were studied by real time PCR-HRM. An efficient amplification of real time PCR products was obtained, and a clear melting curve and appropriate melting peaks for both viruses were achieved in the HRM curve analysis for BoHV type identification. BoHV was identified in all of the isolates and clinical samples, and BoHV types were properly differentiated. Furthermore, viral DNA was detected in 12/18 and 7/18 samples from BoHV-1- and BoHV-5-infected calves, respectively. Real time PCR-HRM achieved a higher sensitivity compared with virus isolation or conventional PCR. In this study, HRM was used as a novel procedure. This method provides rapid, sensitive, specific and simultaneous detection of bovine alpha-herpesviruses DNA. Thus, this technique is an excellent tool for diagnosis, research and epidemiological studies of these viruses in cattle.